2015
DOI: 10.18178/ijlt.1.2.154-160
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Based LMS: An Investigation of User Perceptions and Attitudes

Abstract: This study offers a comprehensive review of various methodologies for emotion based emotion Learning Management Systems (LMS) and examines the use of Technology Acceptance Model (TAM) to investigate how learner beliefs and attitudes influence emotion based LMS use among higher education learners by evaluating the relationships between perceived usefulness, perceived ease of use, attitude and behavioural intentions. In the study, 40 potential users were presented with an introductory demonstration of emotion ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Nwagwu [36] reported availability of limited expertise because there are few technical staff to maintain the operations system. Teoh and Hoe [54] reported that lack of, and inadequately trained personnel as challenge to the use of ICT in most Nigerian higher institutions. Maphalala and Adigun [1] state that academics in the Higher Education Institutions (HEIs) from Africa are plagued by systemic challenges and have limited skills required for the implementation and integration of e-learning.…”
Section: Constraints To Virtual Learning In Nigerian Universitiesmentioning
confidence: 99%
“…Nwagwu [36] reported availability of limited expertise because there are few technical staff to maintain the operations system. Teoh and Hoe [54] reported that lack of, and inadequately trained personnel as challenge to the use of ICT in most Nigerian higher institutions. Maphalala and Adigun [1] state that academics in the Higher Education Institutions (HEIs) from Africa are plagued by systemic challenges and have limited skills required for the implementation and integration of e-learning.…”
Section: Constraints To Virtual Learning In Nigerian Universitiesmentioning
confidence: 99%
“…learning management system (LMS) is a learning platform that students regularly visit; hence, the system's design should provide the students with a positive experience. This is because emotions act as a mood and feeling of a person during the learning process [2]. Emotions are delicate and often influenced by the circumstances in which they occur or their experiences while going through a process.…”
Section: Introductionmentioning
confidence: 99%
“…1, October 2022: 315-327 316 under-standing. Hence, the learning process for the students in LMS will be difficult and affected if they are in a negative mood [2]. Therefore, the LMS, which applies the appropriate emotional design, can evoke positive emotions and lead to positive learning outcomes.…”
Section: Introductionmentioning
confidence: 99%